Standardized Patient Oriented Teaching (SPOT) - Douglas Ander; Joshua Wallenstein; Debra Houry; Sheryl Heron; Tammie Quest; Dahlia Hassani (Association of American Medical Colleges, 2008)
Abstract Delivering bad news is a difficult task for medical practitioners. Whether this is a diagnosis of cancer, miscarriage, losing one's eyesight or death disclosure, it occurs on a daily basis for almost all practicing clinicians. Concerning is the fact that the majority of practicing physicians have received little or no formal training in communicating bad news. In work done at our institution using a standardized patient model to teach death disclosure, only 17 of 37 students reported prior teaching on how to deliver a death disclosure. There currently exist societal and organizational mandates to provide medical students with an education on communication skills, deliverance of bad news, counseling skills, training in recognizing and treating societal problems all in the context of a multi-cultural world. This resource is designed to instruct fourth-year medical students on how to deliver bad news to patients, and provide counseling to victims of intimate partner violence (IPV). In learning how to deliver bad news, students engage in a standardized patient experience where they have to deliver news to a patient injured in a bicycle collision. Students attend a PowerPoint presentation on how to provide counseling for IPV victims that is accompanied by a quiz.